Karakteristik Fresh-Cut Pepaya California Pada Perlakuan Rasio Pati Singkong-Kitosan Dan Jumlah Gliserol Sebagai Edible Coating - Sitorus, Roulina Tiolyn Rohana; Hartiati, Amna; Yoga, I Wayan Gede Sedana (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2025)
Edible coating is a thin, consumable layer that acts as a protective barrier with the ability to inhibit respiration rate, reduce moisture loss, maintain quality, and extend the shelf life of fresh-cut California papaya. This study aimed to determine the effect of the cassava starch–chitosan composite edible coating ratio and glycerol amount on the characteristics of fresh-cut California papaya, as well as to identify the optimal treatment combination during storage. A factorial Completely Randomized Design (CRD) with two factors was used. The first factor was the cassava starch–chitosan composite ratio with three levels: P1 (75:25), P2 (83.33:16.67), and P3 (91.67:8.33); the second factor was the amount of glycerol with three levels: G1 (0.6 g), G2 (0.8 g), and G3 (1 g). These combinations resulted in 9 treatment groups, each replicated three times, with daily observations conducted until the product showed spoilage. The observed variables included weight loss, firmness, total soluble solids, and vitamin C content. The results showed that the edible coating with varying cassava starch–chitosan ratios and glycerol amounts significantly affected weight loss, firmness, total soluble solids, and vitamin C content up to the fifth day of storage, but had no significant effect on these parameters from day six to day ten. Based on physicochemical analysis and the longest shelf life, the treatment with a starch–chitosan ratio of 75:25 and 1 g of glycerol provided the best coating performance during 10 days of storage, with 6.21% weight loss, 2.99 N firmness, 12.23 °Brix total soluble solids, and 49.57 mg/100 g of vitamin C.